Design and Development of Management Information System in Ma'had Huffadz Bilingual Darul Hikmah Malang Using Scrum Method - S Supriyono (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The scrum method is the most important thing in building software. The following research builds a management information system on Ma'had Huffadz Bilingual Darul Hikmah under Darus-Sa'adah Al Mardliyah Foundation. The institution, which is one of the Boarding Schools Tahfidzul Qur'an located in the city of Malang, East Java. The following research uses the Scrum framework. The implementation of the scrum method in the following research uses three sprints. The process of working on each sprint takes no more than a month. The software development in this research is web-based. Work on application programs using the Laravel framework using the PHP programming language. The results showed that the scrum method is very effective in building a boarding school management information system. Scrum is more dynamic, and the results of this scrum implementation can be seen from the system that has been developed. So that by implementing Scrum can produce a system that suits the requirements of the user.